Social capital effects on resilience to food insecurity: Evidence from Kyrgyzstan - Bekhzod Egamberdiev (Journal of International Development, 2024)
This paper investigates the role of social capital in terms of trust and group membership in building household resilience to food insecurity. Using detailed `Life in Kyrgyzstan' multi-topic panel data, the research estimates resilience to food insecurity through the Resilience Index Measurement and Analysis (RIMA) approach, including different pillars and a resilience capacity index. The impact of social capital on resilience pillars and capacity is estimated using IV models for multiple endogenous variables. The results suggest that both trust and group membership positively affect resilience pillars and capacity.
Keywords: 300; food security; instrumental variable; resilience; social capital